Green Betel Leaf Compress as an Effective Therapy for Reducing Breast Engorgement Pain During Lactation - Jannah, Isnaini Nurul; Amalia, Linda; Puspita, Asih Purwandari Wahyoe (FORIKES, 2026)
Breast engorgement is a common condition among lactating mothers, characterized by breast fullness, tightness, and pain. This study aimed to compare the effectiveness of green betel leaf compresses and cabbage leaf compresses in reducing breast pain associated with engorgement. A quasi-experimental pretest–posttest design with two groups was employed, involving 70 breastfeeding mothers who were randomly assigned to either the green betel leaf compress group (n = 35) or the cabbage leaf compress group (n = 35). The intervention was administered twice daily for three consecutive days, with each session lasting 15 minutes. Pain intensity was measured using the Visual Analog Scale before and after the intervention, and participant satisfaction was assessed using a structured questionnaire. The results demonstrated that the mean pain score in the green betel leaf compress group decreased from 5.66 to 0.49, whereas in the cabbage leaf compress group it decreased from 5.54 to 4.31. The Wilcoxon test indicated a statistically significant reduction in pain in both groups (p < 0.001), and the Mann–Whitney test revealed a significant difference in effectiveness between the two interventions (p < 0.001). The mean satisfaction score was higher in the green betel leaf compress group (90.69) compared with the cabbage leaf compress group (59.51). In conclusion, both compress types were effective in reducing breast engorgement pain; however, green betel leaf compresses demonstrated more consistent pain reduction and higher levels of participant satisfaction.Keywords: breast engorgement; green betel leaf compress; cabbage leaf compress; breast pain; breastfeeding mothers